(untitled) (TAJ: Journal of Teachers Association, 2009)
A community based cross-sectional study among the geriatric people i.e. 60 years and above age group was carried out in the rural villages of Rangpur district with a view to find out their common health problems and the relationship between the health problems and some of their socio-economical factors. A total of 1000 geriatric people were interviewed. Among them 73.6% were male and 26.4% were female, majority of them (47.8%) were in the age group 60-64 years and about 30% of them were smokers. About 86% of the respondents were suffering from either a disease or diseases at the time of Interview. The most common diseases suffered by them were arthritis, diarrhoea, hyperacidity and peptic ulcerative diseases, bronchitis, asthma, hypertension, cataract, dental caries, skin disease, diabetes mellitus, hydrocele, etc. A positive relationship of disease prevalence was found with educational status (p< .001), economical status (p<.01) and dependency states (p< .001) of the respondents. Statistically significant relationship was found between dependency state and mental state of the respondents (p< .001). Good relation with other members of the family was found more in independent group (p< .001). This study might provide information to formulate effective preventive and control measures for health problems of the aged. doi: 10.3329/taj.v16i1.3896 TAJ June 2003; Vol.16(1): 15-19